Pemanfaatan Filler Pada Program Siaran Kita Indonesia RRI Jember Sebagai Media Penguatan Pesan: Analisis Berdasarkan Teori Komunikasi Laswell - Hidayatullah, Ach. Ansori; Asmawiranda, Alya; Romadhon, Dzikri; Kholah, Lalu Kharisma Gymnastiar; syafi'i, Imam (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the use of fillers in the Kita Indonesia radio program broadcast by RRI Jember as a means of strengthening communication messages and increasing the engagement of young listeners. The study employs a descriptive qualitative approach, with data collected through observation and interviews with broadcasters and program managers, supported by documentation and relevant literature. The findings indicate that contextually relevant fillers are able to clarify messages, enhance listeners’ understanding, and add educational value to radio programs. Analysis based on Lasswell’s communication model shows that fillers play a role in reinforcing the message element (what) within the communication process. However, the linear nature of Lasswell’s model is limited in explaining the dynamic, two-way interactions characteristic of modern radio programs. This study concludes that fillers are a strategic element in improving the effectiveness of radio communication and recommends continuous evaluation of their use to ensure alignment with program themes and audience needs.